2008
DOI: 10.1080/13880200701741245
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro. Inhibition of Tumor Cell Growth byMiconia fallax.

Abstract: In vitro tumor growth inhibition by the ethanol extract of Miconia fallax DC. (Melastomataceae) was evaluated in culture media containing HeLa cells at the following concentrations: 5, 15, 25, 35, and 45 µg/mL. Bioassay-guided fractionation of this extract furnished a mixture of ursolic and oleanolic acids. Both the ethanol extract and the mixture of the triterpenoid acids produced dose-dependent tumor growth inhibition. This antitumor activity was more pronounced when a mixture of the triterpene acids at a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
11
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 24 publications
3
11
0
1
Order By: Relevance
“…The presence of a C¼O group was revealed by a band at 1708 cm À 1 in the IR spectrum, which was confirmed by the resonance at d 166.6 in the 13 [9] suggested that their structures are closely related, except that the 10-O-(Z)-feruloyl moiety of 1 replaced the 10-O-(E)-feruloyl moiety of (1E,24Z)-1,24-di(feruloyloxy)tetracosane [9]. This was supported by the coupling constant (J (7,8 þ ; calc. 348.9960)).…”
supporting
confidence: 55%
See 2 more Smart Citations
“…The presence of a C¼O group was revealed by a band at 1708 cm À 1 in the IR spectrum, which was confirmed by the resonance at d 166.6 in the 13 [9] suggested that their structures are closely related, except that the 10-O-(Z)-feruloyl moiety of 1 replaced the 10-O-(E)-feruloyl moiety of (1E,24Z)-1,24-di(feruloyloxy)tetracosane [9]. This was supported by the coupling constant (J (7,8 þ ; calc. 348.9960)).…”
supporting
confidence: 55%
“…Their structures were determined by indepth spectroscopic and mass-spectrometric analyses. Among the isolated compounds, oleanolic acid (6), ursolic acid acetate (7), and 3-epibetulinic acid (9) Introduction. -Pachycentria formosana Hayata (Melastomataceae) is an endemic creeping shrub distributed in 300 -2100-m forests throughout Taiwan [1].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As part of our ongoing research on medicinal plants (Cunha et al, 2003(Cunha et al, , 2008Neto et al, 2004), we report herein the in vitro antimicrobial activity of the essential oil obtained from the leaves of R. offi cinalis, as well as the antimicrobial activity of its major constituents, against some important oral pathogens. The essential oil was also characterized by gas chromatography-mass spectrometry (GC-MS) analyses, in order to identify its major components.…”
Section: Antibacterial Activity Of the Essential Oil From Rosmarinus mentioning
confidence: 99%
“…Several pharmacological effects have been attributed to ursolic and oleanolic acids, such as anti-tumor (Cunha et al 2008), anti-inflammatory (Vasconcelos et al 2006), and antimicrobial activities (Cunha et al 2007;Lim et al 2007). In the present study, we evaluate the in vitro and in vivo trypanocidal activity of oleanolic acid and ursolic acid against T. cruzi (Bolivia strain), as well as investigate their acute toxicity on the basis of median lethal dose (DL50) determination and quantification of biochemical parameters.…”
Section: Introductionmentioning
confidence: 98%